Strengthening the Religious Literacy of Kuta Inang Simeulue Cut Village Community through Quarantine Ta'lim Quran Activities - Afandi, Ahmad; Yogi Arya Pratama; Hefrimei Safrisyah; Refan Kananda; M. Dafiq Az-Zikri (ASSUNNAH PRESS, 2023)
This research is motivated by the limited human resources and educational facilities in Kuta Inang Village compared to the community's need for Islamic education. The need for teachers or Quran teachers and educational facilities such as Taman Pendidikan Alquran is still very limited. The aim of this research is to make children accustomed to reciting the Quran, memorizing some short surahs, and daily prayers. In addition, it aims to provide religious lectures by STAI As-Sunnah KKL students to villagers as enlightenment and guidance to continue their enthusiasm for seeking knowledge of Islamic religion. The method applied in this research is Asset Based Community Development (ABCD) with 5 stages of asset reinventing through data collection (observation and FGD), designing types of activities, communicating the activities to potential beneficiaries, implementing the activities, and evaluating them. The results show that participants in the Quranic recitation quarantine have been able to memorize short surahs that they can read during prayer. In terms of performing ablution and prayer, the participants have also mastered the techniques. During the competition, they were very enthusiastic about participating in the activities. From these results, continuity of the activities is needed to address the challenges of limited Islamic teaching in Kuta Inang Village through a collaborative program between the village officials and campus/NGO partners.